2019
DOI: 10.1089/scd.2019.0105
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stromal Cells Are Retained in the Porcine Renal Cortex Independently of Their Metabolic State After Renal Intra-Arterial Infusion

Abstract: The regenerative capacities of mesenchymal stromal cells (MSC) make them suitable for renal regenerative therapy. The most common delivery route of MSC is via intravenous infusion, which is associated with off-target distribution. Renal intra-arterial delivery offers a targeted therapy but limited knowledge is available regarding the fate of MSC delivered via this route. Therefore, we studied the efficiency and tissue distribution of MSC after renal intra-arterial delivery to a porcine renal ischemia reperfusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 46 publications
4
29
0
Order By: Relevance
“…However, the fate of MSC administered in this manner to the kidney is unclear. We previously reported a sharp decline in the number of MSC present in kidney biopsies at 2 weeks after administration of MSC [23]. It is expected that MSC would not stay at the luminal side of microcapillaries, but that these cells are either removed by innate immune cells or migrate to other sites [13,47].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the fate of MSC administered in this manner to the kidney is unclear. We previously reported a sharp decline in the number of MSC present in kidney biopsies at 2 weeks after administration of MSC [23]. It is expected that MSC would not stay at the luminal side of microcapillaries, but that these cells are either removed by innate immune cells or migrate to other sites [13,47].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, direct MSC infusion to the injured tissue may be a better method to deliver MSC to the kidney. We have previously shown that for infusion via the renal artery, MSC are delivered to the microvasculature of the kidney [23]. The interaction with the kidney microvasculature is the starting point for the regenerative effects of MSC, and therefore, it is of key importance to understand the mechanisms of the interaction between MSC and endothelial cells.…”
Section: Introductionmentioning
confidence: 99%
“…29 Similarly, Sierra-Parraga et al recently demonstrated in a pig model of renal IRI that intrarenal arterial infusion of adipose-derived MSC resulted in significant retention up to 8 hours postinfusion, primarily in an intraglomerular distribution with smaller numbers in peritubular capillaries. 30 Although biodistribution results from animal models are likely to be relevant to human subjects, there remains a persistent gap in knowledge of the optimal administration protocols for MSC therapies in AKI.…”
Section: New Insights Into the Localization Survival And Migratory mentioning
confidence: 99%
“…However, the fate of MSC administered in this manner to the kidney is unclear. We previously reported a sharp decline in the number of MSC present in kidney biopsies at 2 weeks after administration of MSC (23). It is expected that MSC would not stay at the luminal side of microcapillaries, but that these cells are either removed by innate immune cells or migrate to other sides (13,47).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, direct MSC infusion to the injured tissue may be a better method to deliver MSC to the kidney. We have previously shown that infusion via the renal artery, MSC are delivered to the microvasculature of the kidney (23). The interaction with the kidney microvasculature is the starting point for the regenerative effects of MSC and therefore it is of key importance to understand the mechanisms of the interaction between MSC and endothelial cells.…”
Section: Introductionmentioning
confidence: 99%